The analysis of losses in protected and non-insulated wires in stationary modes, taking into account weather conditions - E. V. Petrova; S. S. Girshin; V. A. Krivolapov; K. V. Khatsevskiy; V. N. Goryunov; V. M. Trotsenko (Омский научный вестник)
In overhead lines of power supply systems at voltages of 6–110 kV, the use of protected wires is becoming increasingly popular, which have a number of advantages over traditional non-insulated aluminum wires. On the other hand, the presence of insulation requires the development of more complex mathematical models to adequately describe their behavior and study the characteristics of new wires during operation. The results of using the developed mathematical models and calculation programs for comparative analysis of protected and non-insulated wires under conditions of changing load currents and weather conditions are presented. The dependences of temperature and loss of active power on insulation thickness are investigated. It is shown that the presence of insulation allows, under certain conditions, to reduce temperature and losses compared to wires without insulation, all other things being equal. The results obtained can be used to increase the capacity and reliability of power transmission lines.